Spawning New Ideas A Cycle of Discovery. Conference Proceedings of the Annual International Conference of the Association for Experiential Education (24th, Spokane, WA, September 26-29, 1996) - Association for Experiential Education, Boulder, CO.; Baker, Babs; Association for Experiential Education, Boulder, CO. ([S.l.] : Distributed by ERIC Clearinghouse, 1996)
This conference proceedings includes 66 papers, workshop descriptions, and abstracts concerned with experiential education; outdoor education; adventure-based education, counseling, and therapy; and outdoor leadership. Topics include various aspects of program design and administration; experiential educational practices and group facilitation techniques for use with adolescents, families, and corporate teams; community service learning; outdoor learning activities; experiential techniques in teacher education and staff development; gender and racial issues in outdoor and experiential education; team building; group dynamics; spirituality; and adventure and experiential therapy with families, abused adolescents, homeless youth, and emotionally disturbed persons. (SV)
ERIC Note: For selected individual papers, see RC 021 377-394.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adventure Education; Corporate Education; Educational Practices; Educational Strategies; Elementary Secondary Education; Experiential Learning; Group Dynamics; Higher Education; Individual Development; Outdoor Education; Outdoor Leadership; Program Design; Teacher Education; Team Training; Wilderness; Adventure Therapy; Facilitators; Collected Works, Proceedings